Rudesindo García del Rijo paradigm of medicine in Sancti Spíritus - Elizabeth Sánchez Prida; Hansel Leonardo Herrera Rodríguez; Emelina Amiris Llano Gil (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2020)
Antonio Rudesindo García Rijo was a forerunner of endocrinology in Cuba, the objective of the research is to characterize the most important aspects of his work, since he was not only recognized for his extensive medical knowledge, but also for his benefactor and philanthropic attitude, likewise, he sent guidelines in his passage through history in the province of Sancti Spíritus.